Analisis Efektivitas Kinerja Instalasi Pengolahan Air Limbah (IPAL) Rumah Sakit X - Nugroho, Dimas Bagus; Callista Elvania, Nindy; Indah Purwaningrum, Solikhati (Jurnal EnviScience (Environment Science), 2025)
Abstract Hospital wastewater contains pathogenic microorganisms, toxic chemicals, and radioactive substances harmful to health and the environment. Hospital X is a type C hospital with a land area of 10,022 m², a building area of 44,898 m², and 173 beds, generating wastewater with parameters such as TSS, BOD5, COD, ammonia, phosphate, and E. coli. Based on January 2024 testing results at the outlet of the Wastewater Treatment Plant (WWTP), three parameters approached the quality limits set by the East Java Governor Regulation No. 72 of 2013. This condition is due to the WWTP’s long years of operation and new building construction that increased the treatment load. This study aims to identify the characteristics of wastewater and treated water, and to analyze the effectiveness of Hospital X’s WWTP in managing wastewater to be safe for the community and environment. Samples were taken by grab sampling at the inlet and outlet with a volume of 2000 mL. Laboratory results showed ammonia (0.22 mg/L) and phosphate (2.922 mg/L) exceeded quality standards due to insufficient aeration time, causing low dissolved oxygen and inhibiting microorganisms from decomposing NH3 and PO4. The E. coli level (350 MPN/100 mL) met quality standards. Effectiveness calculations showed a significant 96.23% reduction in E. coli, indicating successful disinfection. However, ammonia reduction was only 45.89% and still exceeded limits, while phosphate increased with an effectiveness of -6.22%, indicating phosphate treatment failure. These results highlight the need to optimize aeration and phosphate treatment in Hospital X’s WWTP.